English as a foreign language teachers’ professional success in the Chinese context: The effects of well-being and emotion regulation - Fan, Jian; Wang, Yongliang (Frontiers in Psychology, 2022)
Given the significance of teachers’ professional success in the adequacy of education, exploring the determinants of this variable appears crucial. To address this need, this inquiry inspected the role of well-being and emotion regulation in Chinese EFL teachers’ professional success. For this purpose, 357 Chinese EFL teachers were selected to answer three pre-designed questionnaires. Structural equation modeling (SEM) using Smart-PLS was implemented to analyze teacher participants’ responses. The structural model revealed a strong, favorable connection between well-being, emotion regulation, and professional success. The model also demonstrated that both well-being and emotion regulation were highly influential in Chinese EFL teachers’ professional success. The potential implications for EFL teachers, teacher educators, and educational authorities are further discussed.